Influence of Selected Dietary Plant Extracts on Productive, Physiological, and Viral Immunological Response of Broilers - S. J. Zamil; K. I. A. Al-Shammari; E. M. Mohammed (Tropical Animal Science Journal, 2020)
This experiment was implemented to evaluate the influence of 3 plant extracts involving garlic (GC), cinnamon (CN), and black cumin (BC) powders in broiler chicken diet from 1-42 d on productive, physiological, and immunological traits. In total, 240 birds were assigned into 4 groups, each with 3 replicates. In the control group (CO), the chickens were fed with a balanced diet. Experimental groups were composed by supplementing the diet with 4 mg/kg of diet for each GC, CN, and BC. At 3 and 6 weeks, GC, CN, and BC groups achieved higher body weights, weight gains (p≤0.01), and low feed conversion ratio. GC group recorded low feed intake (p≤0.05) compared to the CO and the other groups from 1 day–6 weeks. GC, CN, and BC groups registered high (p≤0.01) PCV value and lower cholesterol and triglycerides concentrations in serum compared to the CO group. Reduction and increase (p≤0.01) in serum glucose and protein for GC and CN, and CN and BC, respectively, were recorded. High levels of triiodothyronine (T3) (p≤0.05) and thyroid-stimulating hormone (TSH) in GC and CN groups and all treated groups had high concentrations of thyroxine (T4) (p≤0.01) compared to the CO group. Moreover, a clear augmentation in serum antibody titer against Newcastle and Gumboro diseases in GC, CN, and BC compared with the CO group was observed. It was concluded that GC, CN, and BC extracts at the present level may be used to enhance the productive, physiological, and viral immunological characteristics of birds.